Políticas de cotas sociais e paridade de participação no IFRS campus Sertão - Jesus, Édson Régis de (2020)
In 2020, the “Social Quota Law” completed eight years of application in Brazilian federal public education. This work aims to discuss what is one of the most notable public policies of affirmative action for access to federal public education. Legislation, in wishin g to promote social justice, established a 'quota' of 50% of vacancies for graduates of the public system. According to certain theories about justice, the quota system may not be sufficient to guarantee equity in the field of education in the re production of social asymmetries to require actions beyond redistribution. It is in this context that the concept of “parity of participation” by the American political philosopher Nancy Fraser (1947) proves to be a productive path for the analysis of quot as when it demonstrates that 'redistribute' (material), 'recognize' (cultural) and 'represent' (political) are interdependent spheres of the concept of justice. These categories point to certain shortcomings in the quota system when limited to redistributi ve aspects and lead this work to identify the perception of the quota holders of higher education courses at IFRS Campus Sertão as having recognition and representation of the academic population according to their condition. The methodological approach is of a qual itative and quantitative nature, with instruments and procedures of bibliographic documental and field research. The technique and instruments utilized included a questionnaire for the academic population and an interview with quota students. Thi s method o f work contributed to explore the cultural and political dimension of the universe of quota students in terms of recognition and representation in the academic space. The theoretical basis is grounded on authors of the philosophical tradition and on the di scussions of Bourdieu, Passeron and Fraser respectively. The initial hypothesis was partially confirmed. The analyzed data indicate that the Social Quotas Law does not develop all its potential as a space for parity of participation between quota and non q uota students.